verb chapter From the Book of Sharh Al-Kafiya by Allama Jalal Al-Din Muhammad bin Yusuf Al-Halawi Al-Sarai Al-Tabrizi (d. 838AH) - Musleh Al-Majma’i, Khairallah Khamis; Bahloul Al-Jubouri, Nafeh Alwan; Aliwi al-Jubouri, Muwafaq Husayn (Journal of Tikrit University for Humanities, 2023)
Scholarly communication's complexity, conciseness, and clarity contribute to our nation's language weaknesses. The difficulty is exacerbated by this feature and the limited knowledge of many pupils. Individuals' lack of resoluteness and resolve worsens these issues. A sale or a cubit, which made me write in the science of grammar, in the hope that I will serve the nation of Islam as scholars and students with what God has enabled me to do, then one of the prominent grammar masters is the scholar Ibn al-Hajib, and among what we benefited from is his book Al-Mati’: (Explanation of Al-Kafiyah fi grammar) whose phrases are sober, His words are brief, his investigations are valuable, the scholars dealt with him, studied him, and studied him, and he was one of those who opened his closed doors, and paved his expressions for every student of knowledge of the sciences, the imam, the scholar Jalal al-Din Muhammad bin Yusuf al-Halawi al-Tabrizi in his book entitled ((Explanation of the Sufficient for the scholar Jalal al-Din Muhammad bin Yusuf al-Halawi al-Sara’i al-Tabrizi vol. 838AH)) in which he dissolved profanity, subdued phrases, opened closed matters, investigated issues, corrected and corrected, expressed and clarified, and revealed hidden words and structures. The students struggle to understand the material, disrupting cognitive awareness and understanding. The person elaborates on the instances and facts, highlighting their significance. The learner recognizes unclear syntax in these cases. Translation of Al-Mateen (Ibn Al-Hajib). Translation of the commentator (Jalal al-Din Muhammad ibn Yusuf al-Halawi al-Tabrizi). Copying the text according to what was mentioned in the manuscript (Chapter Al-Majroorat only.( Description of transcription. Verification of the text according to the principles of scientific investigation.